ВИСОКОРИЗИЧНИ НОВОРОДЕНИ И ПЕРВАЗИВНИ РАЗВОЈНИ НАРУШУВАЊА - Dukovska Valentina; Duma, Filip; Angelkova Natalija; Avramovska Vesna; Zorcec, Tatjana; Sofijanova, Aspazija; Bojadzieva, Sonja; Popovska, Ana; Spasovska Anastazija (My University, 2017)
Aim of the paper: Analysis of developmental abilities in high-risk infants, with an emphasis on risk, early screening and early diagnosis of disorders of the autistic spectrum (ASD). Materials and methods: Between January 2013 and Decembеr 2015, a total number of 612 high - risk infants, were followed as outpatients at the Clinic for neurology and development. We used Griffiths developmental scales for assessment of developmental abilities and M-CHAT (Modified Checklist for Autism in Toddlers) when there was a suspicion for ASD. Results: In 4,4% of the children disorder in the field of socialization, social development and speech, as well as symptoms of ASD were found. The median age of the infants during examination was 23 months. Each child had a normal neurological status. Using the developmental tests, Griffiths developmental scales, the examined children, showed normal development of gross motor skill and normal development of fine motor skills. The developmental coefficient in the area of social development was 64%, and 44% in the area of speech. Four children showed clear signs of sensory integration dysfunction. 3,3% of children with symptoms of ASD were conceived with IVF, were twins and were preemies. Conclusion: The goal of developmental follow-up and developmental diagnostics should be establishing the risk and symptoms of ASD in high - risk children, especially in premature infants and twins.
Keywords: high-risk infants; autistic spectrum; early diagnostics; developmental tests; early intervention